Adsorption Isotherms of Tryptophan Enantiomer on D-Tryptophan Molecular Imprinted Polymer - Jin, Y.; Liu, C.C.; Sun, X.H.; Lee, K.J.; Jung, Y.A.; Row, K.H. (Asian Journal of Chemistry, 2012)
A molecular imprinted polymer using D-tryptophan as a template and methacrylic acid and acrylamide as a functional co-monomer was prepared. Water and methanol were used as the hydrophilic porogen with ethylene glycol dimethacrylate as the crosslinker and 2,2'- azobis(isobutyronitrile) as the initiator. Comparison of D and L form of tryptophan adsorption isotherm on molecular imprinted polymer was made by the static method. The experimental parameters in the equilibrium isotherms were estimated by linear and nonlinear regression analyses. The linear equation for concentration and sorbents to adsorption concentrations was then expressed and the adsorption equilibrium data were correlated into Langmuir, Freundlich, quadratic, Allometric, Langmuir and Freundilich extension isotherm models. The calculated data is well fitted with the experimented data. The D-tryptophan imprinted polymer showed extraordinarily higher adsorption ability for D-tryptophan than the L-tryptophan compounds that were also assessed. Furthermore, the competitive Langmuir isotherms were applied to the mixture compounds of D and L form tryptophan.